2014
DOI: 10.1007/s11033-014-3538-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D receptor FokI and ApaI polymorphisms with lung cancer risk in Tunisian population

Abstract: Many studies reported that Vitamin D Receptor (VDR) gene polymorphisms might influence the cancer risk due to their antiproliferative, antiangiogenic, and apoptotic effects. The aim of this study was to explore the genetic association of VDR polymorphisms with lung cancer risk in Tunisian population. The genotype and haplotype frequencies of four VDR polymorphisms, FokI (rs2228570), BsmI (rs1544410), ApaI (rs7975232) and TaqI (rs731236) were studied using polymerase chain reaction and restriction fragment leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
3
18
0
1
Order By: Relevance
“…It is worth noting that all the VDR genotypes were related to declined NSCLC risk. An increased risk comparing TT vs. CC in Taq1 in our study is consistent with the results observed in previous studies [50,51,52]. On the other hand, there are a few other studies that have also found no association with increased risk [53,54].…”
Section: Discussionsupporting
confidence: 93%
“…It is worth noting that all the VDR genotypes were related to declined NSCLC risk. An increased risk comparing TT vs. CC in Taq1 in our study is consistent with the results observed in previous studies [50,51,52]. On the other hand, there are a few other studies that have also found no association with increased risk [53,54].…”
Section: Discussionsupporting
confidence: 93%
“…ii) A-C-T (rs1544410-rs7975232-rs731236) (OR 5 5.82, p 5 0.008). 13 Our results are consistent with the possible association of rs1544410-rs731236 (BsmI-TaqI) haplotype and lung cancer risk. Further investigation on a larger group of patients is needed to confirm this association with lung cancer risk.…”
Section: Discussionsupporting
confidence: 90%
“…In a recently report of 240 lung cancer patients and 280 healthy individuals from the North African population, Kaabachi et al showed a significantly increased risk of lung cancer among carriers of the rs2228570 (FokI) variant. There was no significant association with lung cancer risk of the rs1544410 (BsmI) and rs731236 (TaqI) 13 polymorphisms.…”
Section: Discussionmentioning
confidence: 88%
“…The remaining 9 literatures were included in this meta-analysis because accordance with the inclusion criteria. [24,[26][27][28][29][30][31][32][33] The flow chart of literature selection process is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%